Requirement Analysis for Cybersecurity Solutions in Industry 4.0 Platforms - Ilhan, Ismail; Karakose, Mehmet (Ieee, 2019)
Increasing technology and the use of the Internet have brought the Industry 4.0 revolution. Internet of Things, smart devices, smart objects, information, and data are in many systems in an era of developing the technology. The main components of the industry 4.0 such as cyber-physical system, the Internet of objects, big data and cloud computing has some of the challenges. One of these is cybersecurity. In this study, the structure of the technologies in industry 4.0 and cybersecurity requirement analyzes of these technologies were discussed. With the given recommendations, it is expected to use these technologies in Industry 4.0 safely. Finally, the necessary measures against cyber-attacks and risks in developing technologies and the use of security systems were discussed.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 21-22, 2019 -- Inonu Univ, Malatya, TURKEY
Keywords: Cybersecurity; solution; industry 4.0; requirement analysis